Ghrelin receptor antagonism of morphine-induced conditioned place preference and behavioral and accumbens dopaminergic sensitization in rats - Jerabek, Pavel; Havlickova, Tereza; Puskina, Nina; Charalambous, Chrysostomos; Lapka, Marek; Kacer, Petr; Sustkova-Fiserova, Magdalena (Neurochemistry international, 2017)
An increasing number of studies over the past few years have demonstrated ghrelin's role in alcohol, cocaine and nicotine abuse. However, the role of ghrelin in opioid effects has rarely been examined. Recently we substantiated in rats that ghrelin growth hormone secretagogue receptors (GHS-R1A) appear to be involved in acute opioid-induced changes in the mesolimbic dopaminergic system associated with the reward processing. The aim of the present study was to ascertain whether a ghrelin antagonist (JMV2959) was able to inhibit morphine-induced biased conditioned place preference and challenge-morphine-induced accumbens dopaminergic sensitization and behavioral sensitization in adult male rats. In the place preference model, the rats were conditioned for 8 days with morphine (10 mg/kg s.c.). On the experimental day, JMV2959 (3 and 6 mg/kg i.p.) or saline were administered before testing. We used in vivo microdialysis to determine changes of dopamine and its metabolites in the nucleus accumbens in rats following challenge-morphine dose (5 mg/kg s.c.) with or without JMV2959 (3 and 6 mg/kg i.p.) pretreatment, administered on the 12th day of spontaneous abstinence from morphine repeated treatment (5 days, 10-40 mg/kg). Induced behavioral changes were simultaneously monitored. Pretreatment with JMV2959 significantly and dose dependently reduced the morphine-induced conditioned place preference and significantly and dose dependently reduced the challenge-morphine-induced dopaminergic sensitization and affected concentration of by-products associated with dopamine metabolism in the nucleus accumbens. JMV2959 pretreatment also significantly reduced challenge-morphine-induced behavioral sensitization. Our present data suggest that GHS-R1A antagonists deserve to be further investigated as a novel treatment strategy for opioid addiction.
Keywords: glycin; Animals; Conditioning, Operant; Morphine; Analgesics, Opioid; Rats, Wistar; triazoly; Nucleus Accumbens; Dopamine; operantní podmiňování; Microdialysis; mikrodialýza; Receptors, Ghrelin; opioidní analgetika; Triazoles; Male; nucleus accumbens; krysa rodu Rattus; dopamin; Glycine; morfin; zvířata; mužské pohlaví; Rats; receptory ghrelinu; potkani Wistar